OPTIMALISASI PENGGUNAAN LEGO DALAM PEMBELAJARAN MATEMATIKA SMP UNTUK MENDUKUNG IMPLEMENTASI KURIKULUM 2013 - Rejeki, Sri (WARTA, 2016)
kill about using LEGO in mathematics teaching and learning to mathematics teachers. This conducted into three stages of training and two stages of real teaching. The stages of the training were introducing the use of LEGO in mathematics teaching and learning, designing sets of teaching and learning activities using LEGO as the media, and peer teaching. The real teaching conducted in two stages of three meetings for each stages. Twelve mathematics teachers from five schools of Muhammadiyah in Surakarta were participated in this training. The teachers have technically trained with new experiences using LEGO as media in mathematics learning and have developed five sets of lesson plans for the topics of fractions, sets, proportion, linear equation with one variable, and statistics. The real teaching for the topic of fractions was conducted in two of those five schools. The results indicate the learning activities designed support students understanding and attitude in mathematics.Â Â Â